2017
DOI: 10.18632/oncotarget.18540
|View full text |Cite
|
Sign up to set email alerts
|

A novel pan-Nox inhibitor, APX-115, protects kidney injury in streptozotocin-induced diabetic mice: possible role of peroxisomal and mitochondrial biogenesis

Abstract: NADPH oxidase (Nox)-derived reactive oxygen species (ROS) are increasingly recognized as a key factor in inflammation and extracellular matrix accumulation in diabetic kidney disease. APX-115 (3-phenyl-1-(pyridin-2-yl)-4-propyl-1-5-hydroxypyrazol HCl) is a novel orally active pan-Nox inhibitor. The objective of this study was to compare the protective effect of APX-115 with a renin-angiotensin system inhibitor (losartan), the standard treatment against kidney injury in diabetic patients, on streptozotocin (STZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Our previous studies completed in both type 1 and 2 diabetic mice demonstrated that APX-115 has a comparative renoprotective effect to losartan (a mainstay treatment in DKD) and GKT137831 (a dual Nox inhibitor) respectively [17,18]. Particularly, the present study provides additional confirmatory evidence in another murine model and shows the dose-dependent effect of APX-115 in diabetic kidney injury.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our previous studies completed in both type 1 and 2 diabetic mice demonstrated that APX-115 has a comparative renoprotective effect to losartan (a mainstay treatment in DKD) and GKT137831 (a dual Nox inhibitor) respectively [17,18]. Particularly, the present study provides additional confirmatory evidence in another murine model and shows the dose-dependent effect of APX-115 in diabetic kidney injury.…”
Section: Discussionsupporting
confidence: 74%
“…Nox family is one of the major contributors on ROS generation in the kidney [10]. Our previous studies with db/db and STZ-induced mice have implied increases of protein and mRNA levels of renal Nox 1, 2, and 4, which were significantly reduced by APX-115, a panNox inhibitor [17,18]. We consistently showed that excessive oxidative stress was significantly attenuated by APX-115, particularly at dose of 5 and 30 mg/kg, as well as losartan.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Kidney specimens from CKD patients show decreased PGC‐1α expression (Han et al, ; Sharma et al, ), which is associated with a decreased GFR in human kidney fibrosis (Lemos et al, ). PGC‐1α is decreased in various models of CKD, including unilateral ureteral obstruction‐induced fibrosis (Han et al, ), db/db diabetic mice (Hong et al, ; Kim, Lee, et al, ; Kim, Lim, et al ; Long et al, ; Yuan et al, ; Zhang, Liu, Zhou, Wang, & Chen, ), and streptozotocin‐induced diabetic mice (Kwon et al, ). Our results also show that PGC‐1α expression is significantly decreased in diabetic mice (Figure ).…”
Section: Protective Effect Of Pgc‐1α In Kidney Diseasementioning
confidence: 99%